»The Other«, Refugee Crisis and Online Hate Speech - Kopytowska, Monika; Stawikowska-Marcinkowska, Agnieszka (Hassrede – ein multidimensionales Phänomen im interdisziplinären Vergleich, 2020)
The article focuses on online hate speech targeting the Other in Poland and Germany. The authors address the question of who is the Other and why this Other becomes an object of stereotypes, prejudice and verbal aggression. They discuss the definitions of hate speech, its linguistic characteristics, legal instruments, as well as the structural-functional features of communication within cyberspace facilitating the spread of this phenomenon. The analysis covers Polish and German online comments following YouTube videos published in 2015–2017 and selected with the use of the following keywords: “refugees”, “immigrants”, “Muslims”. Pointing to the universality of certain linguistic tools and strategies present in hate speech targeting the above-mentioned groups, the authors also discuss the role of historical, legal and socio-economic factors in both countries.